Cost-Effectiveness of Lorlatinib as a First-Line Therapy for Untreated Advanced Anaplastic Lymphoma Kinase-Positive Non-Small Cell Lung Cancer - Li, SiNi; Li, JianHe; Peng, LiuBao; Li, YaMin; Wan, XiaoMin (Frontiers in Oncology, 2021)
Introduction: Recently, a phase III CROWN trial compared the efficacy of 2 Anaplastic lymphoma Kinase (ALK) inhibitor and demonstrated that lorlatinib displayed a clinical improvement than crizotinib for advanced non-small cell lung cancer (NSCLC) patients. So, the aim of this study was to estimate the cost-effectiveness of lolatinib as first-line therapy for patinets with advanced ALK-positive (+) NSCLC. Materials and Methods: A cost-effectiveness analysis was performed using a microsimulation model from the US payer perspective and a lifetime horizon (30-year) in patients with previous untreated advanced ALK+ NSCLC. Based on the CROWN trial, patients’ characteristics were obtained and the transition probabilities were estimated. All direct costs were derived from the official sources and published literatures. The main outcome of the model was total costs, incremental cost-effectiveness ratio (ICER), quality-adjusted life years (QALYs), and life years (LYs). One-way and probabilistic sensitivity analyses were conducted to test the robustness of model outcomes, along with multiple scenario analyses. Results: In base case analysis, in which 1 million patients were simulated, treating with lorlatinib or crizotinib in the first line was related to a mean cost of $909758 and $616230 (Incremental cost: $293528) and a mean survival of 4.81 QALYs and 4.09 QALYs (Incremental QALY: 0.72) per patient, respectively. The main driver of cost effectiveness were drug price and subsequent cost. PAS indicated that lorlatinib vs crizotinib have 90% cost-effectiveness when increasing the willingness-to-pay (WTP) threshold to $448,000/QALY. And Scenario analysis demonstrated that lorlatinib vs crizotinib treatment have 100% cost-effectiveness at WTP threshold of 200,000/QALY when decreasing the price of lorlatinib to 75% ($424.5) of its original price. Conclusions: In this study, lorlatinib is unlikely considered cost effective compared with crizotinib for patients with previous untreated advanced ALK+ NSCLC at WTP threshold of 200,000/QALY.